oxLDL and eLDL Induced Membrane Microdomains in Human Macrophages - Wallner, Stefan (PLoS One, 2016)
BACKGROUND: Extravasation of macrophages and formation of lipid-laden foam cells are key events in the development and progression of atherosclerosis. The degradation of atherogenic lipoproteins subsequently leads to alterations in cellular lipid metabolism that influence inflammatory signaling. Especially sphingolipids and ceramides are known to be involved in these processes. We therefore analyzed monocyte derived macrophages during differentiation and after loading with enzymatically (eLDL) and oxidatively (oxLDL) modified low-density lipoproteins (LDL). METHODS: Primary human monocytes were isolated from healthy, normolipidemic blood donors using leukapheresis and counterflow elutriation. On the fourth day of MCSF-induced differentiation eLDL (40 μg/ml) or oxLDL (80 μg/ml) were added for 48h. Lipid species were analyzed by quantitative tandem mass spectrometry. Taqman qPCR was performed to investigate transcriptional changes in enzymes involved in sphingolipid metabolism. Furthermore, membrane lipids were studied using flow cytometry and confocal microscopy. RESULTS: MCSF dependent phagocytic differentiation of blood monocytes had only minor effects on the sphingolipid composition. Levels of total sphingomyelin and total ceramide remained unchanged, while lactosylceramides, cholesterylesters and free cholesterol decreased. At the species level most ceramide species showed a reduction upon phagocytic differentiation. Loading with eLDL preferentially increased cellular cholesterol while loading with oxLDL increased cellular ceramide content. Activation of the salvage pathway with a higher mRNA expression of acid and neutral sphingomyelinase, neutral sphingomyelinase activation associated factor and glucosylceramidase as well as increased surface expression of SMPD1 were identified as potentially underlying mechanisms. Moreover, flow-cytometric analysis revealed a higher cell-surface-expression of ceramide, lactosylceramide (CDw17), globotriaosylceramide (CD77), dodecasaccharide-ceramide (CD65s) and GM1 ganglioside upon oxLDL loading. ApoE in contrast to apoA-I preferentially bound to the ceramide enriched surfaces of oxLDL loaded cells. Confocal microscopy showed a co-localization of acid sphingomyelinase with ceramide rich membrane microdomains. CONCLUSION: eLDL leads to the formation of lipid droplets and preferentially induces cholesterol/sphingomyelin rich membrane microdomains while oxLDL promotes the development of cholesterol/ceramide rich microdomains via activation of the salvage pathway.